Thành phần hóa học và hoạt tính ức chế enzym α-glucosidase của lá vối Việt Nam (Cleistocalyx operculatus Roxb. Merr. et Perry) - Tố Chinh, Trương Thị; Giang, Phan Minh (Vietnam Journal of Chemistry, 2016)
Three flavones: 2',4'-dihydroxy-6'-methoxy-3',5'-dimethylchalcone (2), kaempferol (8), quercetin  (9); five terpenoids: betulin (4), betulinic acid (5), oleanolic acid (6), maslinic acid (7), Axit arjunolic (10), together with 1-tetratriacontanol (1) and β-sitosterol (3) were isolated from the leaves of Cleistocalyx operculatus Roxb. Merr. et Perry. Their structures were determined by means of spectroscopic methods. The extract of its leaves showed α-glucosidase inhibition activity. Keywords. Cleistocalyx operculatus; Myrtaceae; flavone; terpenoid; α-glucosidase inhibition, NMR